Urinary quality of life in patients treated with prostate SBRT with intra-prostatic boost - Bhargava, Nisha; Hurwitz, Martina; Levey, Josephine; Bennett, Lily; Aronovitz, Joseph A.; Schmidt, Daniel R.; Dawson, Liana; Lischalk, Jonathan W.; Kaplan, Irving D.; Aghdam, Nima (Frontiers in Oncology, 2025)
Purpose/objectivesSBRT is a standard of care treatment for localized prostate cancer. Whole gland dose escalation remains controversial. Concomitant intraprostatic boost (IPB) may offer an acceptable compromise for dose escalation. In this series, we report changes in International Prostate Symptom Scores (IPSS) over a 12-month period following SBRT with IPB in patients treated in a large academic institution.Materials/methodsSeventy-four patients treated from October 2018 to March 2022 with robotic stereotactic body radiotherapy completed IPSS questionnaires. IPSS were evaluated for patients at three timepoints: pre-treatment, post-treatment (defined as 3 months after SBRT completion), and at follow-up (defined as within 12 months after SBRT completion). The patients were stratified into two cohorts: patients who experienced minimally important difference (MID) in their post-treatment IPSS and those who did not. Urethral and bladder doses were retrospectively extracted from the treatment planning software and compared between the two cohorts using Wilcoxon rank sum test.ResultsOf the 74 patients, 46 (62%) experienced MID in scores (cohort A), while 28 (38%) did not (cohort B). Patient characteristics in the two cohorts such as risk stratification and initial PSA were well-balanced. Median IPSS for cohort A were 5 (range: 0–21) pre-treatment, 12 (range: 3–28) post-treatment, and 8 (range: 1–32) at 12 months. For cohort B, the scores were 9.5 (range: 0–29), 7 (range: 1–19), and 8.5 (range: 0-32), respectively. In addition, there was a statistically significant difference in D0.03cc to the bladder in cohort A compared to cohort B (41.9 Gy vs 40.2 Gy; p < 0.001).ConclusionIPB is well tolerated with acceptable change in urinary quality of life metrics as measured by IPSS. Max dose to the bladder remains the only significant difference in patients who experienced MID in their urinary quality of life.